Context and interdisciplinarity in entrepreneurship research. Do you see the elephant? - Tegtmeier, Silke (Piccola Impresa / Small Business, 2023)
Purpose. This editorial argues for putting emphasis on context and interdisciplinarity in entrepreneurship and innovation research. Design/methodology/Approach. I propose a conceptual discussion about the topic. Findings. Following Welter (2011), this editorial shows that entrepreneurship and innovation need to be contextualized, that contexts can be intertwined, and that recursive relationships may exist. The case of gendered innovations strikingly demonstrates the role of context and supports the argument that diversity in entrepreneurship and innovation asks for specific targeted research. Pratical and social implications. To properly research complex phenomena, such as entrepreneurship and innovation, this also calls for more interdisciplinary research in this field. Exemplarily, the decisive role entrepreneurs' voices play in presenting their business case to relevant gatekeepers supports the argument of making contributions to expand knowledge in this field following an interdisciplinary approach in research. The Elaboration Likelihood Model (Petty & Cacioppo, 1984, 1986a, b) as a dual-process model is presented as an example to highlight a contribution from research on attitude formation to the field of entrepreneurship.